Corporate well-being programme as a tool to cope with reduced engagement and resilience in Covid-19 times. - Núñez-Sánchez, José Manuel (Association of Economists and Managers of the Balkans – UdEkoM Balkan, 2022)
The coronavirus pandemic is having a dramatic impact on employees around the world, damaging their physical and psycosocial well-being and triggering disengagement and affecting their resilience. the aim of this research is to test, through a real case study, the effects of a corporate wellness programme on engagement and resilience in COVID-19 times. A quantitative methodology has been used through self-administered questionnaires and two instruments the reduced International Physical Activity Questionnaire (IPAQ), to measure the level of physical activity, and the Healthy Employee Questionnaire to measure engagement and resilience. The results reveal that a corporate well-being programme, adapted to COVID-19 times, offers better relationship between physical activity levels and engagement and resilience, compared with other pre-pandemic programmes, proving its efficiency. As a conclusion, this case study results may be helpful to convince organizations of the importance of adapting their corporate well-being programmes in pandemic times, to maintain and even improve the engagement and resilience of their workforce.
Selected paper at 6th International Scientific Conference EMAN. Economics & Management: How to Cope with Disrupted Times
Keywords: Trabajadores - Salud mental; Trabajo - Aspectos psicológicos; Gestión de personal - Aspectos psicológicos; COVID-19; Engagement; Resilience; Corporate well-being